Legal Protection of the Trade Name and its Impact on Consumer Protection from Fraud and Deception (A Comparative Study) - Aburumman, Amer Ali (Dirasat: Shari’a and Law Sciences, 2022)
Objectives: The study aims to compare trademark and trade name handled by the Registrar of trademarks or the Registrar of trade names, and the problem that arises there is a trading name similar to this trademark or a trade mark similar to this trade name in the records, especially to determine the criterion for comparing them under Article (8/9) of the trademark law, and paragraphs (C, D) of Article (5) of the trade names Law. Methods: The study followed the comparative analytical descriptive approach. The researcher analyzed the legal texts regulating the comparison between the trademark and the trade name, some of the problems resulting from it, and the statement of the proposed legal amendments. Results: The trade name was set up to distinguish the commercial store, while the trademark was set up to distinguish products or services. The case law has established that it is impossible to compare the trade name and the trademark and that the protection is for the entire trade name. Conclusions: Adopting the main part of the trade name when comparing it with the trademark, taking into account the uses of the trademark and the trade name, verifying the possibility of the public falling into fraud and deception due to the similarity between them. Additionally, we need to take into account using and verifying as much as possible the possibility of the public falling into fraud and deception due to the similarity between them.